2014
DOI: 10.18061/1811/61596
|View full text |Cite
|
Sign up to set email alerts
|

Civic Community Theory and Rates of Violence: A Review of Literature on an Emergent Theoretical Perspective

Abstract: Civic community theory has emerged in the last 10 years as a middle range theory to explain community variation in rates of crime. It has proven to be particularly powerful for explaining variations in violent crime across rural communities in the U.S. This essay provides a review of the available published literature testing components of the theory. The three main conceptual dimensions of the civic community thesis are outlined, and the nature of the empirical evidence is evaluated. The essay concludes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…For instance, researchers sometimes take organizations and institutions as indirect or proxy measures of civic engagement or social cohesion. Thus, while churches as a whole might or might not reduce crime (Doucet & Lee, 2014; Sampson, 2012), several studies have shown that the presence of “bridging” denominations (e.g., mainstream Protestants, Catholics) reduces crime, while the presence of “bonding” denominations (e.g., Evangelical Protestants) increases crime (Beyerlein & Hipp, 2006; Desmond, Kikuchi, & Morgan, 2010; Lee & Bartkowski, 2004; Wo et al, 2016). Some local institutions like cafes, recreation centers, and community policing are associated with lower crime, while other institutions like bars or payday lenders are associated with higher crime (Kubrin & Hipp, 2016; Papachristos, Smith, Scherer, & Fugiero, 2011; Peterson & Krivo, 2010; Wo, 2016).…”
Section: Collective Resources Community Organizations and Violent Crimementioning
confidence: 99%
“…For instance, researchers sometimes take organizations and institutions as indirect or proxy measures of civic engagement or social cohesion. Thus, while churches as a whole might or might not reduce crime (Doucet & Lee, 2014; Sampson, 2012), several studies have shown that the presence of “bridging” denominations (e.g., mainstream Protestants, Catholics) reduces crime, while the presence of “bonding” denominations (e.g., Evangelical Protestants) increases crime (Beyerlein & Hipp, 2006; Desmond, Kikuchi, & Morgan, 2010; Lee & Bartkowski, 2004; Wo et al, 2016). Some local institutions like cafes, recreation centers, and community policing are associated with lower crime, while other institutions like bars or payday lenders are associated with higher crime (Kubrin & Hipp, 2016; Papachristos, Smith, Scherer, & Fugiero, 2011; Peterson & Krivo, 2010; Wo, 2016).…”
Section: Collective Resources Community Organizations and Violent Crimementioning
confidence: 99%